2015
DOI: 10.5812/ircmj.24685
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Weight and Female Sexual Dysfunction: A Case Control Study

Abstract: Background:Obesity is rapidly increasing worldwide with negative effects on women’s health, psychosocial factors and quality of life. Female sexual dysfunction (FSD) is a major public health problem that is worrying for many women physically, emotionally and socially.Objectives:The purpose of this study was to investigate the association of body weight with FSD and sexual satisfaction, in Ilam, western Iran, in 2010 to 2011.Patients and Methods:This was a case-control study on 120 women aged 18–50 years [64 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 36 publications
3
32
1
4
Order By: Relevance
“…They also believe that the pelvic floor muscle may be negatively affected by the body weight, favoring a possible SD [27]. This statement may be reinforced by age range in the study (18-75 years old), since there was significant difference in both groups for BMI and sexual function [26,28]. In the present study, SD frequency represented 22% of women with an average age of 35 years old, and most of them were college graduates.…”
Section: Discussionsupporting
confidence: 50%
“…They also believe that the pelvic floor muscle may be negatively affected by the body weight, favoring a possible SD [27]. This statement may be reinforced by age range in the study (18-75 years old), since there was significant difference in both groups for BMI and sexual function [26,28]. In the present study, SD frequency represented 22% of women with an average age of 35 years old, and most of them were college graduates.…”
Section: Discussionsupporting
confidence: 50%
“…There is a negative influence of Body Mass Index towards sexual functions. More Body Mass Index will lead to sexual dysfunction this is in accordance to the study done by Mozafari et al, 2015 that studies on the relation of body weight and female sexual function using Female Sexual Function Index Score. It is found that there is an inverse upside relation between BMI and Female Sexual Function Index Score.…”
Section: Body Mass Index Effect On Thesupporting
confidence: 87%
“…Depression could also be influenced by the increasing of BMI because more BMI or women who are suffering from obesity will cause body image perception that would influence the woman's psychological side that would affect their sexual desire (Mozafari et al, 2015).…”
Section: Depression Factor Influence On Thementioning
confidence: 99%
See 2 more Smart Citations